1985
DOI: 10.1007/bf00491924
|View full text |Cite
|
Sign up to set email alerts
|

Daily intake of selenium by bottle-fed infants in Belgium

Abstract: The selenium content of commercial infant formulae, processed milk and beikost was measured by hydride generation atomic absorption spectrometry after previous wet acid digestion. The median daily intake by infants (1-6 months) fed milk, soya or cereal-based infant formulae was 3.0-7.8 micrograms/day; lower than the mean daily intake by Belgian breast-fed infants (6.1-8.6 micrograms/day) and cow's milk bottle-fed infants (7.6-10.8 micrograms/day).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
3
4
0
1
Order By: Relevance
“…The concentration range in this study is similar to those found by other authors in Europe and America, and lower than in infant formulae studied from Asia (15,17,18,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (table 5).…”
Section: Selenium Contentssupporting
confidence: 89%
“…The concentration range in this study is similar to those found by other authors in Europe and America, and lower than in infant formulae studied from Asia (15,17,18,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (table 5).…”
Section: Selenium Contentssupporting
confidence: 89%
“…Our data are comparable with the Se levels in milk in some other European countries, such as Austria (14), Belgium (32), Spain (33), Sweden (10), and Finland up to the mid1980s (30,34). In some other countries in Europe [Greece, Germany, Estonia, Scotland, Italy, and Finland (after selenium fertilization)], the Se levels in mature milk are much higher (4,13,35,36). Although our results show uniform distribution of Se in human milk in different parts of Poland, other authors have shown that Se levels in mature human milk may show considerable geographic variation.…”
Section: Discussionsupporting
confidence: 84%
“…Selenium intake by breast-fed infants. In countries where the Se level in milk is around 10 ng/mL (in Poland), the Se intake varies from 5 to 8 µg/day (8,12,32,36). Our data show that the Se intake by breast-fed infants in Poland does not meet the recommended daily allowances.…”
Section: Discussionmentioning
confidence: 72%
“…Our data are comparable with the Se levels in milk in some other European countries, such as Austria (14), Belgium (32), Spain (33), Sweden (10), and Finland up to the mid-1980s (30,34). In some other countries in Europe [Greece, Germany, Estonia, Scotland, Italy, and Finland (after selenium fertilization)], the Se levels in mature milk are much higher (4,13,35,36). Although our results show uniform distribution of Se in human milk in different parts of Poland, other authors have shown that Se levels in mature human milk may show considerable geographic variation.…”
Section: Discussionsupporting
confidence: 84%